Nonlinear behaviour of back-to-back gapped built-up cold-formed steel channel sections under compression - Roy, K.; Ting, T.; Lau, Hieng Ho; Lim, J. (Elsevier, 2018)
© 2017 Elsevier Ltd In cold-formed steel structures, such as trusses and portal frames, the use of back-to-back gapped built-up cold-formed steel channel-sections for column members are becoming increasingly popular. In such an arrangement, the lowest flexural buckling mode may not necessarily be overall buckling of the whole column. In the literature, only three test results have been previously reported for such cold-formed steel columns, and limited to values of non-dimensional slenderness ranging from 1.08 to 1.16. This issue is considered herein. The results of 40 experimental tests are reported, conducted on back-to-back gapped built-up cold-formed steel channel-sections covering the range of non-dimensional slenderness from stub to slender columns. A nonlinear finite element model is then described that shows good agreement with the experimental results. The finite element model is then used for the purposes of a study comprising 84 models. Using the experimental and finite element results, it is shown that design in accordance with the American Iron and Steel Institute (AISI) and Australian and New Zealand Standards (AS/NZS) can be conservative by as much as 53%. However, use of a modification to the non-dimensional slenderness, that considers the gap, results in the design standards being within 5% conservative with respect to the experimental and finite element results.